Analyzing gay terms in Brazilian Portuguese subtitles from the movie The Boys in the Band - Brezolin, Adauri (Transletters. International Journal of Translation and Interpreting, 2021)
The Boys in Band was one of the first American movies to thrust gay characters into the limelight, giving visibility to their way of acting, dressing, and speaking. In this article, I analyze gay male terms used by the characters in the original film (1970), and in its 2020 remake. My selection includes the lexical items “fag”, “faggot”, “faggy”, “fairy”, “gay”, “homosexual”, “nelly”, “pansy”, “queen”, “queer”, and “sissy”, all representative of camp (Harvey, 1998). My main goal is to verify how they were transposed into Brazilian Portuguese, and to what extent they can equate to camp talk from the pragmatic viewpoint. Apart from these terms, my analysis will include other linguistic resources able to shape the identity of this group of speakers. After introducing the main features of the film (Cohen, 2015; Bell, 2016), I will discuss gay issues and camp talk (Harvey, 1998/2000; Martínez Pleguezuelos, 2017); next, I will compare the data mainly focusing on their evaluative load (Hughes, 2006; Valdeón, 2010). My results have demonstrated that, in the target language, the terms analyzed were consistently used and largely equated with the evaluative load of their source counterparts.